Comparison of protein quality of three seaweed species (Sargasum polycystum, Sargasusum oligocystum and Ulva pertusa) from Panay and Guimaras Island, Philippines for potential use in milkfish feed - Arnaiz, Regina Marielle T. (2016.)
Aquafeed production is the largest expenditure in intensive aquaculture operations, contributing to about 40-60% of total costs (Yildrim et al., 2009; Akiyama et al., 1992 cited in Ali et al., 2009). This is mostly due to the ingredients being used, particularly the protein source fishmeal (Millamena, 2002). The variable and finite supple of fishmeal, however, result in high costs, prompting the search for cheaper alternative ingredients as a priority in cost reduction practices regarding the production of aquafeeds (Attala and Mikhail, 2008). Seaweeds have known nutritional values, and are naturally abundant in Philippine waters, thus their potential could be tapped to reduce costs in aquaculture and could therefore maintain the sustainability of the industry (Shields and Lupatsch, 2012; Trono, 1999). In this study, the protein quality of two brown seaweeds (Sargassum polycystum and Sargassum oligocystum) and one green seaweed (Ulva pertusa) was evaluated by determining their crude protein content, inhibitory activities against trypsin and chymotrypsin, and in vitro protein digestibility. Among the three species, the green seaweed U. pertusa has the highest crude protein content at 23.43%. The obtained crude protein content was 8.28% for S. polycystum and 9.22% for S. oligocystum. Trypsin inhibition of the seaweeds ranged from 54-57%, and chymotrypsin inhibition was from 57-64%. Total phenolic content (TPC) was highest in S. polycystum, and lowest in S. oligocystum. In vitro protein digestibility action of milkfish gut enzyme was highest in S. oligocystum (92.30 ± 2.80), followed by the observed digestibility in U. pertusa (75.01 ± 2.14), and lowest in S. polycystum (64.99 ± 8.11). Determination of Pearson?s correlation (r) showed a negative correlation (r=-0.99, p=0.08) existing between the TPC and %RPD values. Based on the results, among the threes species, U. pertusa with 23.43% crude protein content and a %RPD of 75.01% has a potential for partial inclusion in aquafeeds to reduce costs.
Thesis -- Bachelor of Science in Chemistry. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Seaweed; Trypsin; Chymotrypsin; Phenolic content; Protein digestibility